DAMPAK ON-THE-JOB TRAINING DI LUAR NEGERI PADA STRATEGI PEMBELAJARAN BAHASA INGGRIS DAN KEMAMPUAN SOFT SKILLS MAHASISWA - Aniroh, Kun (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2011)
Globalization opens up the chances for students of hotel studies to have on-the-job training at hotels abroad with the duration of six months up to one year. At the first three months the students got difficulties in using their English and get less interaction and appropriate behavior because in a hotel abroad there are many staffs from many countries using English with different accents and different cultures. Such environment triggered students to learn English with a particular strategy that lead them to improve their English and their soft skills convincingly.